CHALLENGES IN THE DIAGNOSIS AND DIFFERENTIATION OF THYROID HORMONE RESISTANCE FROM TSHOMA - Lai, Shu Xian; Lau, Eunice Yi Chwen (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Introduction An elevated fT4 with non-suppressed TSH levels may present as a diagnostic challenge resulting in inappropriate treatment. Although rare, resistance to thyroid hormone (RTH) and TSHomas can present in this manner and diagnosis is important to guide management. Case A 43-year-old male was referred from a district hospital for evaluation of atypical chest pain. He was noted to have an elevated fT4 with normal TSH for the past four years and had received carbimazole previously. He reported symptoms of hyperthyroidism including intermittent palpitations, tremor and anxiety. No goitre was noted clinically. Both his mother and maternal aunt had undergone thyroid surgery. After stopping treatment, he had elevated fT4 (28.31 and 19.39 pmol/L) and normal TSH (1.55 and 1.619 m IU/L) performed on two different platforms. Sex hormone binding globulin (22.6 nmol/L), alpha-subunit (0.22 IU/L) and neck ultrasound were normal. Pituitary MRI showed an ill-defined hypoenhancing nodule measuring 2.0 mm x 2.2 mm x 1.9 mm. Other pituitary hormones were unremarkable. He went on to have a thyrotropin stimulation test which showed an exaggerated TSH response with an 11-fold increase at 20 minutes, supporting the diagnosis of RTH. Genetic testing was not performed due to resource limitations. Subsequently, he was managed symptomatically with beta blockers. Conclusion When managing discordant thyroid function tests, a high index of suspicion and proper clinical assessment, including laboratory and imaging studies, are needed to ensure precise diagnosis and avoid potentially harmful or unnecessary treatment such as radioactive iodine, anti-thyroid medication or pituitary surgery. Small nonfunctioning pituitary adenomas are not uncommon. Abnormal imaging needs to be correlated carefully.